2020
DOI: 10.15698/mic2020.10.732
|View full text |Cite
|
Sign up to set email alerts
|

Variants of the human RAD52 gene confer defects in ionizing radiation resistance and homologous recombination repair in budding yeast

Abstract: RAD52 is a structurally and functionally conserved component of the DNA double-strand break (DSB) repair apparatus from budding yeast to humans. We recently showed that expressing the human gene, HsRAD52 in rad52 mutant budding yeast cells can suppress both their ionizing radiation (IR) sensitivity and homologous recombination repair (HRR) defects. Intriguingly, we observed that HsRAD52 supports DSB repair by a mechanism of HRR that conserves genome structure and is independent of the canonical HR machinery. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 97 publications
(139 reference statements)
0
6
0
Order By: Relevance
“…Previously a RAD52 S346* truncation was associated with reduced breast cancer risk in carriers of germline BRCA2 mutations [ 22 ]. Subsequent experiments have shown that the S346* truncation affects RAD52 oligomerization and HR repair when expressed in budding yeast [ 70 ]. This truncation also shows decreased nuclear localization because it loses the C-terminus domain where the NLS sequences are ( Fig 3 ) [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously a RAD52 S346* truncation was associated with reduced breast cancer risk in carriers of germline BRCA2 mutations [ 22 ]. Subsequent experiments have shown that the S346* truncation affects RAD52 oligomerization and HR repair when expressed in budding yeast [ 70 ]. This truncation also shows decreased nuclear localization because it loses the C-terminus domain where the NLS sequences are ( Fig 3 ) [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…This truncation also shows decreased nuclear localization because it loses the C-terminus domain where the NLS sequences are ( Fig 3 ) [ 22 ]. In human cells but not budding yeast S346* also shows SSA defects [ 22 , 70 ]. The authors suggest that in the absence of BRCA2 function, repair relies on RAD52 which promotes mutagenic SSA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations